Effects of training-induced fatigue on pacing patterns in 40-km cycling time trials - Skorski, S.; Hammes, D.; Schwindling, S.; Veith, S.; Pfeiffer, M.; Ferrauti, A.; Kellmann, M.; Meyer, T. (Medicine & Science in Sports & Exercise, 2015)
Introduction: In some endurance sports, athletes complete several competitions within a short period, resulting in accumulated fatigue. It is unclear whether fatigued athletes choose the same pacing pattern (PP) as when they have recovered.